(untitled) (Fiep Bulletin - online, 2011)
Nowadays, the number of cases of violence has been responsible for a growing demand for care in public health services, especially in emergency units. This is an article of reflection, which aims to reflect on the dynamic interaction between health professionals and victims of violence during the process of care in emergency rooms. The process of taking care of health professionals suffers changes, which may be differentiated, depending on the placement of professional ethics, leading to major ethical and moral dilemmas in emergency services. Therefore, we conclude that the consolidation of a quality care for victims of violence is necessary to: identify the main obstacles faced during the care, establishing a support network of referral services for cases of violence, development of institutional routines for each type of violence, establishment of better working conditions of health professionals, especially those in the emergency room.